2020
DOI: 10.1093/ecco-jcc/jjz203.497
|View full text |Cite
|
Sign up to set email alerts
|

P368 Tofacitinib induction efficiency and intracellular cytokine dynamics in ulcerative colitis: Results from clinical practice

Abstract: Background Tofacitinib is an oral JAK inhibitor approved for the treatment of ulcerative colitis (UC). Its efficiency was proven in registration trials; however, data from clinical practice are insufficient. Our aim was to evaluate response to tofacitinib after 8 weeks in UC patients, and to assess potential predictors of response including early cytokine production shifts. Methods Data from consecutive UC patients who starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Of the 202 citations identified with the search strategy, 17 studies including 1162 patients with UC were eligible to be included in this review. [5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Supplementary Table 1). Six studies were reported as full-text articles, and 11 were conference proceedings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 202 citations identified with the search strategy, 17 studies including 1162 patients with UC were eligible to be included in this review. [5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Supplementary Table 1). Six studies were reported as full-text articles, and 11 were conference proceedings.…”
Section: Resultsmentioning
confidence: 99%
“…Mucosal healing was reported in 6 studies 5,7,12,15,18,19 (n = 252; Figure 3). Mucosal healing was achieved in 41.9% of patients at week 8 (95% CI, 18.1-65.6; range, 23.1%-54.2%; 3 studies 12,15,18 ) and in 35.1% of patients at weeks 12 to 16 (95% CI, 11.5-58.7; range, 9.1%-64.9%; 4 studies 5-7, 15, 19 ).…”
Section: Mucosal Healingmentioning
confidence: 99%
“…Kolar et al identified an early decrease in IL-4 levels as a potential biomarker of tofacitinib response. 85 In another study, a tofacitinib-specific mucosal genetic biomarker was identified that was significantly correlated with endoscopic response. The identified hub gene (p=1.5×10 −9 , fold change 2.3) had a predictive accuracy for the response of 100% (p<0.001).…”
Section: Biomarkers Predicting Responsementioning
confidence: 99%
“…A retrospective cohort study from Prague included 24 patients with UC, including 25% patients who were bio-naïve. 20 After 8 weeks of tofacitinib 10 mg BID, mucosal healing [endoscopic Mayo sub-score ≤1] was demonstrated in 52.9% of the patients. In responders, the mean [±SD] total Mayo score decreased from 5.9 [±3.5] to 1.1 [±1.3] [ p = 0.01], the mean endoscopic sub-score decreased from 2.0 [±1.0] to 0.6 [±0.7] [ p = 0.02], the mean CRP dropped from 6.7 [±6.2] to 2.0 [±2.2] mg/L [ p = 0.04], and the mean faecal calprotectin level dropped from 1195 [±1189] to 578 [±654] µg/g [ p = 0.05].…”
Section: Introductionmentioning
confidence: 99%